2011
DOI: 10.4081/mr.2011.e5
|View full text |Cite
|
Sign up to set email alerts
|

Does CCR5 gene-D32 deletion protect C.trachomatis infected Indian women from tubal pathology?

Abstract: Deletion in chemokine receptor CCR5 gene is reported to prevent development of tubal pathology among Dutch Caucasian C. trachomatis infected women. Hence, a pilot study was undertaken, to evaluate the involvement of CCR5 gene in tubal pathology among Indian women with or without Chlamydia infection. Three hundred women with or without Chlamydia infection and with different reproductive manifestations were screened for CCR5 gene using a standardized PCR. Only 6 C. trachomatis infected women without tubal block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The CCR5 32 deletion was genotyped by detecting size differences in the amplicons on 3% agarose gel; wild type (WT) CCR5 gene with 189 bp product, homozygote CCR5 mutant gene with 157 bp, and the heterozygote CCR5 gene with both 189 and 157 bp products. [3] No homozygous or heterozygous deletion was observed in CCR5 gene; all were with wild type gene [Figure 2a]. Our observation on complete absence of CCR5∆32 deletion is consistent with a report from a north Indian population.…”
Section: Individuals or Couples Attending The Integratedsupporting
confidence: 89%
See 1 more Smart Citation
“…The CCR5 32 deletion was genotyped by detecting size differences in the amplicons on 3% agarose gel; wild type (WT) CCR5 gene with 189 bp product, homozygote CCR5 mutant gene with 157 bp, and the heterozygote CCR5 gene with both 189 and 157 bp products. [3] No homozygous or heterozygous deletion was observed in CCR5 gene; all were with wild type gene [Figure 2a]. Our observation on complete absence of CCR5∆32 deletion is consistent with a report from a north Indian population.…”
Section: Individuals or Couples Attending The Integratedsupporting
confidence: 89%
“…Our observation on complete absence of CCR5∆32 deletion is consistent with a report from a north Indian population. [4] Although a previous study has shown a 2% heterozygous CCR5∆32 deletion in 300 studied women, these 6 women belonged to the Muslim community, [3] as was reported among the Muslims of northern India. In the present study none of the subjects were Muslim.…”
Section: Individuals or Couples Attending The Integratedmentioning
confidence: 82%
“…However, the sample size used in this specific analysis was limited ( n = 41 in total), and this result must be considered with prudence. Moreover, the CCR5∆32 was not a protective factor of tubal pathology development in C. trachomatis ‐infected women in a subsequent study that evaluated 174 women with reproductive problems (99 positive for C. trachomatis ) and 126 fertile women (42 positive for C. trachomatis ), both groups from India (Mania‐Pramanik, Kerkar, Vallabhadas, Mehta, & Salvi, 2011).…”
Section: Ccr5 and Ccr5δ32 In Bacterial Infectionsmentioning
confidence: 99%